NUTRIENT ABSORPTION OF SACHA INCHI (Plukenetia volubilis L.) IN DEFINITIVE FIELD IN THE PROVINCE OF SAN MARTÍN, PERU - PICHIS-GARCÍA, Roger Aban Hader (2024)
Sacha inchi has a high content of polyunsaturated fatty acids and is a promising crop for local communities and the food industry. However, to improve its production and quality, it is essential to understand its nutritional requirements, so the objective of this study was to evaluate the nutrient uptake, growth and yield of sacha inchi in final field in the province of San Martin, Peru. They used a randomized complete block design with three treatments and four replicates, applying ammonium nitrate (NH4NO3), triple superphosphate Ca(H2PO4)2 and potassium chloride (KCl), in three doses: T0 = control, T1= medium dose and T2= high dose, and five samplings of botanical parts. Treatment T2 showed better results compared to the other treatments, showing that nitrogen, phosphorus and calcium (N-P-Ca) were the most absorbed macronutrients and sodium, iron and manganese (Na-Fe-Mg) were the most absorbed micronutrients. This treatment also showed better results in the growth and yield of the crop. Finally, they were able to determine the nutrients most used by sacha inchi in each of the phenological stages evaluated, improving the growth and yield of the crop, demonstrating the great importance of mineral nutrition in plants.